Knowledge and the constitution of society: Dead ends and ways forward in the sociology of knowledge. (November 2013) - Walsh, Philip
This paper discusses the roots of knowledge society theory – an emerging paradigm within theoretical sociology – in classical sociology of knowledge, and draws some conclusions about the former's validity, relevance and shortcomings. The paper first presents a framework for understanding the development of classical sociology of knowledge, and positions knowledge society theory within this tradition by connecting it to the earlier theory of post-industrial society. It is argued that, while knowledge society theory has much to recommend it in terms of its effectiveness in challenging existing orthodoxies about the relationship between society and knowledge, it has not sufficiently differentiated itself from the theory of post-industrial society and falls prey to some of the problems that it has itself raised against this theory. This problem can, however, be mitigated by connecting knowledge society theory with some of the positive theoretical developments that are beginning to emerge from the agency–structure debate.